2022
DOI: 10.1039/d2ra04735g
|View full text |Cite
|
Sign up to set email alerts
|

Universal and ultrasensitive detection of foodborne bacteria on a lateral flow assay strip by using wheat germ agglutinin-modified magnetic SERS nanotags

Abstract: A universal SERS-based lateral flow assay was proposed for highly sensitive detection of foodborne bacteria in food and environmental samples using wheat germ agglutinin-modified Fe3O4@Au nanotags.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…An alternative approach is the use of SERS tags to achieve a sensitive detection with the spectra of Raman reporter molecules as label‐based methods. The SERS tags are usually composed of nanoparticles modified with capture probes to target bacteria with a Raman reporter molecule 33–35 . This approach has the potential to detect multiple bacteria simultaneously.…”
Section: Bacterial Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative approach is the use of SERS tags to achieve a sensitive detection with the spectra of Raman reporter molecules as label‐based methods. The SERS tags are usually composed of nanoparticles modified with capture probes to target bacteria with a Raman reporter molecule 33–35 . This approach has the potential to detect multiple bacteria simultaneously.…”
Section: Bacterial Detectionmentioning
confidence: 99%
“…Raman spectroscopy can be used with other technologies to improve the performance of the assay, such as lateral flow assays (LFAs) and microfluidics. Several studies combined SERS with lateral flow immunoassay for the detection of different bacteria 34,41,43 . Lateral flow assays offer the advantages of low costs, real‐time analysis, and portability.…”
Section: Bacterial Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This interface creates new possibilities for producing a POC device for rapid clinical caries screening in future and demonstrates wide ranging potential in the clinical diagnosis of dental diseases. Tu et al [ 139 ] reported a universal surface-enhanced Raman scattering (SERS)-based lateral flow assay (LFA) using wheat germ agglutinin-modified, Au-modified magnetite nanocomposites for the detection of foodborne bacteria in food and environmental samples with high sensitivity. The proposed universal detection method was effectively utilized for the accurate and specific detection of three foodborne bacteria with a low detection limit (10 cells mL −1 ) and a short testing time (<8.14%).…”
Section: Diagnostic Application Of Mnpsmentioning
confidence: 99%
“…3,4 Notably, it poses a significant risk to global food safety, public health and can result in substantial economic losses. 5 The listeriosis cases have surged yearly, with up to 30% mortality rate for Listeria sepsis among the high-risk groups, including children, the elderly, pregnant women, and patients with malignancy, organ transplants, or other immunocompromised states. 6 Listeria sepsis represents onethird of adult cases of invasive listeriosis.…”
Section: ■ Introductionmentioning
confidence: 99%